24.6k views
3 votes
If r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to (r/s)(6)

If r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to (r/s)(6)-example-1
User Jahred
by
5.3k points

2 Answers

4 votes

The correct options for this question are missing: Here are the options:


1) 3(6) - 1/ 2(6) + 1


2) (6) / 2(6) + 1


3) 36 - 1/26+1


4) (6) - 1/(6) + 1


Answer:


r(x) = 3x - 1


s(x) = 2x + 1


The ratio for r/s(x) will be equal to 3x - 1/2x + 1


and for this x will be equal to 6


now we will put in the value of x in the equation


3(6) - 1/ 2(6) + 1



So for this question the answer is the first option


3(6) - 1/ 2(6) + 1



User Ottobar
by
5.5k points
4 votes

Answer:

r(6)/s(6) = 3(6) -1

--------------

2(6) +1

Explanation:

r(x) = 3x-1

Let x=6

r(6) = 3(6) -1

s(x) = 2x+1

Let x=6

s(6) = 2(6) +1

r(6)/s(6) = 3(6) -1

--------------

2(6) +1

User Sobo
by
5.8k points